Antonio Gaudí master architect - Bassegoda Nonell, Juan (Abbeville Press, 2000)
"In this enlightening volume, a concise, knowledgeable text by the director of the Royal Gaudí Chair at the Polytechnical University of Catalonia (Barcelona) combines with striking images by a well-known architectural photographer to provide a new perspective on Gaudí's remarkable career. The text covers the full range of his oeuvre, describing early assignments in the 1870s as a draftsman for leading architects in Barcelona, the innovative buildings he created for the Güell Palace and Estate, daring new structural solutions at Bellesguard, architecture inspired by nature at the Casa Calvet and in the Park Güell, and the construction of his unfinished masterpiece, the Church of the Sagrada Familia, which occupied him until his death. The author traces all the influences that led to his definitive style, from his fascination with the Orient and neogothicism to his affinity for naturalism and specific geometric forms."--Provided by publisher.